Die Industrielle Entwicklung in Connecticut: Rezession oder Strukturkrise? - Breuer, Helmut (ERDKUNDE, 1973)
This article discusses some necessary and possible structural changes in fully developed industrial regions and the corresponding spatial problems. In order to be able to comprehend such variations it is important to observe the individual components of the process of change. One important question is wether and to what extent declining or departed manufacturing industries can be replaced by substitute industries. In North America, besides Pennsylvania, it is the highly developed industrial regions of the New England states which were or are being subjected to the processes of change. During recent decades metalworking, electrical and non-electrical engineering and the aerospace industry have taken the leading role, particularly in Massachusetts and Connecticut. The construction of transport equipment (helicopters, jet engines, submarines, and space vehicles) has a particularly strong concentration in Connecticut. These industries rely to a great extent on government contracts, often of tremendous size. Sudden cutbacks of such contracts due to the diminishing involvement in Vietnam, the curbing of the space programme, and the general unfavorable economic state hit Connecticut's economy severely. The state's rate of unemployment rose in 1970-1972 to one of the highest in the country. The lay-off of highly skilled workers, the regional concentration of unemployment in mature industrial towns and problems of creating new jobs in growing manufacturing industries are discussed. More coordinated effort and planning to attain regional structural improvements seem necessary.